2013
DOI: 10.1590/s0102-311x2013000400014
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the day of the week of hospital admission on the prognosis of stroke patients

Abstract: This study aimed to evaluate the weekday and weekend distribution of stroke case hospital admissions and their respective prognosis based on a sample from the Estudo de Mortalidade e Morbidade do Acidente Vascular Cerebral (EMMA), a cohort of stroke patients admitted to a community hospital in the city of São Paulo, Brazil. We ascertained all consecutive cases of first-time strokes between April 2006 and December 2008 and performed a subsequent one-year follow-up. No association was found between frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A “weekend effect” in patients with cerebrovascular disease is reported with heterogeneous results. 8 16 A study utilized the Nationwide Inpatient Sample (NIS) from 2004 and showed 12% increased risk of death with weekend admissions. 13 A second study using data from Get With the Guidelines—Stroke program also demonstrated 19% increased mortality in weekend admissions among patients with hemorrhagic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…A “weekend effect” in patients with cerebrovascular disease is reported with heterogeneous results. 8 16 A study utilized the Nationwide Inpatient Sample (NIS) from 2004 and showed 12% increased risk of death with weekend admissions. 13 A second study using data from Get With the Guidelines—Stroke program also demonstrated 19% increased mortality in weekend admissions among patients with hemorrhagic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…This cohort was the first one to demonstrate the prognosis value of multimorbidity using CCI in long-term survival in a stroke cohort in Latin America. EMMA study is an ongoing stroke cohort, which demonstrated several stroke outcomes mentioned in previous publications in the last decade [10,23,29,30,31,32]. The study population in EMMA comes from a low-income area with poor public health support in the city of São Paulo located in Brazil.…”
Section: Discussionmentioning
confidence: 99%